Bamboo-Based Biochar: A Still Too Little-Studied Black Gold and Its Current Applications - Silvana Alfei; Omar Ginoble Pandoli (MDPI AG, 2024)
Biochar (BC), also referred to as "black gold", is a carbon heterogeneous material rich in aromatic systems and minerals, preparable by the thermal decomposition of vegetable and animal biomasses in controlled conditions and with clean technology. Due to its adsorption ability and presence of persistent free radicals (PFRs), BC has demonstrated, among other uses, great potential in the removal of environmental organic and inorganic xenobiotics. Bamboo is an evergreen perennial flowering plant characterized by a short five-year growth period, fast harvesting, and large production in many tropical and subtropical countries worldwide, thus representing an attractive, low-cost, eco-friendly, and renewable bioresource for producing BC. Due to their large surface area and increased porosity, the pyrolyzed derivatives of bamboo, including bamboo biochar (BBC) or activated BBC (ABBC), are considered great bio-adsorbent materials for removing heavy metals, as well as organic and inorganic contaminants from wastewater and soil, thus improving plant growth and production yield. Nowadays, the increasing technological applications of BBC and ABBC also include their employment as energy sources, to catalyze chemical reactions, to develop thermoelectrical devices, as 3D solar vapor-generation devices for water desalination, and as efficient photothermal-conversion devices. Anyway, although it has great potential as an alternative biomass to wood to produce BC, thus paving the way for new bio- and circular economy solutions, the study of bamboo-derived biomasses is still in its infancy. In this context, the main scope of this review was to support an increasing production of BBC and ABBC and to stimulate further studies about their possible applications, thus enlarging the current knowledge about these materials and allowing their more rational, safer, and optimized application. To this end, after having provided background concerning BC, its production methods, and its main applications, we have reviewed and discussed the main studies on BBC and ABBC and their applications reported in recent years.